Calibration of low-cost triaxial magnetometer - Kuncar Ales; Sysel Martin; Urbanek Tomas (MATEC Web of Conferences, 2016)
Heading angle of magnetic compasses is estimated using the triaxial magnetometer readings. The accuracy of these readings is influenced by many factors such as sensor errors (scale factors, non-orthogonality, and offsets), and magnetic deviations (soft-iron and hard-iron interference). To calculate the true heading angle, the magnetic calibration of magnetometer is necessary. This research paper describes a calibration procedure for triaxial low-cost MEMS magnetometer. The proposed calibration method determines twelve calibration parameters in 3D arbitrary rotations of magnetometer.